Breeding season of the South American fur seal (Arctocephalus Australis, Otariidae: Carnivora): New data for establishing independent evolutionary histories? - Pavés, Héctor J. (2016)
The South American fur seal (SAFS) is distributed from Peru (Pacific Ocean) to Uruguay (Atlantic Ocean). However, there is a section of coastline of about 2,300 km along the Chilean coast where no SAFS are recorded. Based on morphological comparisons 3 geographic forms have been reported (Peruvian, South Chilean, Atlantic), whereas preliminary genetic studies suggest the presence of 3 distinct genetic types (Peruvian, South Chile, Atlantic). However, both of these approaches are support only the existence of 2 independent evolutionary histories for SAFS (Peruvian, Atlantic), in which case, we would also expect to find some differences in the species' life histories among these locals populations (e.g., in the timing of the breeding season). In this study, we compare the breeding seasons of SAFS at Punta Pichalo (19°36'S-Chile), Isla Guafo (43°33'S-Chile), and Isla de Lobos (35°01'S-Uruguay) with data published for Punta San Juan (15°21'S-Peru). The periods for establishing territories, pupping, and mating took place on similar dates at Isla Guafo and Isla de Lobos, but occurred about a month earlier at Punta Pichalo and Punta San Juan. Pupping peaked at Isla Guafo on 15-December, at Isla de Lobos on 17-December, and at Punta Pichalo on 27-November. These differences in timing were not related to demographic, oceanographic or photoperiod conditions of the breeding sites under study, neither is related with the latitudinal effects on the breeding phenology. Based on results, we suggest that certain characteristics of life history can help identify species with independent evolutionary histories.